SELEKSI PENETAPAN KANDIDAT POHON PLUS PENAGE CALLOPHYLUM INOPHYLUM L.) DI KECAMATAN MATAN HILIR SELATAN KABUPATEN KETAPANG - yanti, Robi; Muin, Abdurrani; Wulandari, Reine Suci (JURNAL HUTAN LESTARI, 2015)
Panage is a plant that grows in the edge of the shore and at this time is still the natural vegetation. This research has been conducted on Tanjung Batu beach and Among beach in south Matan Hilir sub-district in November – December 2014. This research was conducted to found penage trees which meets the eligibility criteria as a candidate of the best tree, and to find penage trees as a candidate of the best tree in south Matan Hilir sub-district. This research was conducted by Exploratory method. Data collected includes total tree height, bole height, extensive canopy (height and diameter of the canopy), rod diameter, and fruit production. The result was found 5 the best trees on Tanjung Batu beach and 5 the best trees candidate on Among beach. Total tree height which is at score of 20 is 4 trees and the percentage difference 189%, 186%, 163%, and 162%. The highest percentage result from total tree height on Tanjung Batu beach (189%). Whereas from Among beach the highest percentage at bole height score us 15 with difference percentage 216%, and extensive botanical score us 10 with difference percentage 261%. Most of the penage tree with diameter 20 above are at scores 30 with the highest percentage 271% in Tanjung Batu beach. It show penage trees in south Matan Hilir sub-district qualifies as the best trees. Keyword :tree recovery, the best penage tree, penage fruit production.